ANALISIS SISTEM PENGENDALIAN INTERN ATAS PERSEDIAAN BERAS PADA PERUM BULOG KANSILOG LUBULINGGAU - Dewi Anggraini; Yuli Nurhayati; Muhammad Rio Agusman (LPPM Universitas Bina Insan, 2020)
This research was carried out at the Lubuklinggau Kansilog Bulog General Corporation with the aim of the study to analyze the internal control system of rice supplies in the Peruvian Lubuklinggau Bulog Kansilog. The research method used in this study is a qualitative method. The results of the study can be concluded that the internal control system at the Lubuklinggau City Logistics Section (Kansilog Office) has carried out procedures and is able to divide the authority and responsibility of each section, in addition to making decisions taken by the leadership so that in determining the inventory there is a collaboration of each part, the logistics department know and assess the amount of rice stock in addition to the marketing department that has documents related to the expenditure of rice in the Logistics Office (Kansilog) Lubuklinggau City, then the internal control system is needed in determining the value of inventory with the method used is the first entry and first exit method so that the value the available stock is known by the warehouse department in collaboration with the marketing department to seek the availability of rice at the Lubuklinggau City Logistics Section (Kansilog Office).